Assessing Emergency Medical Services Readiness for Disaster and Crisis Response: A Systematic Review" - Meshari Saud Doeb Alotaibi; Naif Abdullah Saad Alotaibi; Fahad Abduliziz Alarifi; Abdulaziz Naif Alotaibi; Garnes Halal Alotaibi; Sultan Sanad Alotaibi; Sattam Khalaf Alotaibi; Khaled Assaf Nahar Alotaibi; Faleh Mosaib Alotaibi; Sultan Aeyd Nasser Alaotibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
n critical situations, such as emergencies and disasters, Emergency Medical Services (EMS) personnel, including paramedics, EMTs, and other frontline workers, play a vital role in providing immediate medical care. Effective disaster management hinges on preparedness, making it crucial for EMS providers to be adequately prepared for such events. This systematic review aims to comprehensively assess the level of readiness among EMS providers in responding to emergencies and disasters by analyzing peer-reviewed journal articles published between 2005 and 2023. A comprehensive search will be conducted across major databases, including Scopus, Web of Science, PubMed, and Google Scholar, to identify relevant research on emergency and disaster preparedness within the EMS context. To our knowledge, this study represents the first comprehensive evaluation of EMS provider readiness in disaster scenarios. This research will delve into key aspects of disaster preparedness among EMS providers and explore strategies for enhancing their readiness levels. A critical step in developing effective tools to assess and improve EMS provider disaster readiness lies in identifying the core components of preparedness.